2020
DOI: 10.1038/s41368-020-00087-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy targeting cancer stem cells “awakens” them to induce tumour relapse and metastasis in oral cancer

Abstract: Radiotherapy is one of the most common treatments for oral cancer. However, in the clinic, recurrence and metastasis of oral cancer occur after radiotherapy, and the underlying mechanism remains unclear. Cancer stem cells (CSCs), considered the "seeds" of cancer, have been confirmed to be in a quiescent state in most established tumours, with their innate radioresistance helping them survive more easily when exposed to radiation than differentiated cancer cells. There is increasing evidence that CSCs play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 167 publications
(230 reference statements)
1
86
0
12
Order By: Relevance
“…While chemotherapy and radiotherapy may help reduce the risk of recurrence, they induce life-altering side effects and fail in a significant fraction of patients. As a result, most metastatic cancers arise from previously treated non-metastatic disease ( 371 373 ).…”
Section: Il-12 Delivery Strategiesmentioning
confidence: 99%
“…While chemotherapy and radiotherapy may help reduce the risk of recurrence, they induce life-altering side effects and fail in a significant fraction of patients. As a result, most metastatic cancers arise from previously treated non-metastatic disease ( 371 373 ).…”
Section: Il-12 Delivery Strategiesmentioning
confidence: 99%
“…CSCs are considered to be the "seeds" of tumors. CSCs have a significant role in tumor relapse, metastasis, resistance against therapy, and are targets for cancer treatment (108). Several studies have demonstrated that specific circRNAs can influence CSCs in HCC by different mechanisms.…”
Section: Circrnas Regulate the Stemness Of Cancer Cells In Hccmentioning
confidence: 99%
“…MiRNAs that were identified as radiosensitizing include Let-7 (Wang, Yuan, et al 2013), miR-7 (Lee et al 2011), miR-15a/15b, miR-16 (Mei et al 2015), miR-22 (Zhang et al 2017), miR-27a (Ren et al 2015), miR-124 (Fu and Xiong 2016), miR-125b (Metheetrairut et al 2017), miR-129-5p (Luo et al 2015), miR-139-5p (Pajic et al 2018), miR-142-3p (Troschel et al 2018, miR-148b (Lai et al 2018), miR-155 (Gasparini et al 2014), miR-185 (Chai et al 2017;Liu et al 2019), miR-200c (Lin et al 2013Sun et al 2015;Wang et al 2019), miR-205 (Zhang et al 2014), miR-218 (Hu et al 2019), miR-302 (Liang et al 2013), miR-449-5p (Zhang et al 2020), miR-634 (Yang et al 2020), miR-671-5p (Tan et al 2019) and miR-770-5p (Lee et al 2017). An obvious similarity among all these radiosensitizing miRNAs is that many of these miRNAs were shown to be able to regulate downstream targets which are involved in the regulation of cellular growth and invasion such as EGFR/PI3K/Akt1 (miR-7) (Lee et al 2011;Liang et al 2013), STAT3 (miR124 and miR-634) (Fu and Xiong 2016;Yang et al 2020), Jun-1 (miR-125b) (Metheetrairut et al 2017), HMGB1 (miR-129-5p) (Luo et al 2015), STXBP4 (miR-200c) (Liu et al 2019), HSPA1A (miR-449-5p) (Zhang et al 2020), FOXM1 (miR-671-5p) (Tan et al 2019) and PBK (miR-770-5p) (Lee et al 2017).…”
Section: Roles Of Mirnas In Mediating Treatment Response Toward Radiotherapy In Breast Cancermentioning
confidence: 99%
“…In contrast, a substantially lower number of miRNAs were reported to be involved in regulating invasion and metastases (4 miRNAs), cell cycle checkpoints (3 miRNAs), autophagy (2 miRNAs), and cancer cell stemness development (1 miRNAs) (Figure 3(B)). Of note, the latter four cellular processes also play essential roles in contributing to radioresistance development Taylor et al 2018;Liu et al 2020). Features such as enhanced proliferation, DNA repair capability, invasion, metastases, and resistance toward radiotherapy are characteristics of CSCs.…”
Section: Roles Of Mirnas In Mediating Treatment Response Toward Radiotherapy In Breast Cancermentioning
confidence: 99%